PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN IKLIM ORGANISASI TERHADAP KINERJA GURU DAN IMPLIKASINYA PADA MUTU SEKOLAH SMK SWASTA KABUPATEN PANDEGLANG PROVINSI BANTEN - Dinata, Ata Iskandar (Gapenas Publisher, 2025)
School quality reflects the effectiveness of principal leadership, organizational climate, and teacher performance as key actors in the learning process. This study aims to analyze the influence of principal leadership and organizational climate on teacher performance and its implications for school quality in private vocational high schools (SMK) in Pandeglang Regency, Banten Province. The research employs a quantitative approach with Partial Least Square-Structural Equation Model (PLS-SEM) analysis techniques. The sample consists of 224 teachers from 14 private vocational schools selected proportionally. The findings indicate that principal leadership has a positive and significant effect on teacher performance (coefficient 0.568) and school quality (coefficient 0.301). Organizational climate also significantly influences teacher performance (coefficient 0.283) and school quality (coefficient 0.423). Furthermore, teacher performance significantly contributes to school quality with a coefficient of 0.295. The results also confirm that teacher performance acts as a partial mediator in the relationship between principal leadership and school quality, as well as between organizational climate and school quality. This study concludes that improving school quality can be achieved through optimizing principal leadership, creating a conducive organizational climate, and enhancing teacher professionalism. The main recommendations include strengthening academic supervision, fostering a collaborative organizational culture, and providing continuous training for principals and teachers to improve the quality of vocational education in Pandeglang Regency